ANALISIS PERISTIWA PENYEBAB PADA KETERLAMBATAN PROYEK APARTEMEN - Rosdianto, Moch Afif; Suef, Mokh; Angreni, Endah (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
A Project could be told success if it had a capability to fulfill a project’s goal, which was project could be done either in time or do not have a major lateness. Many things were affecting project buildings processing. This research purpose was to analyze whose causing lateness for apartment buildings project event in Surabaya. To analyze so many cause lateness event would be needed a systematic method approach. This research’s method was used a Fault Tree Analysis (FTA) Method which was used to seek cause event and the probability of lateness. Not only two of those methods, but also expert judgment technique was conducted by using questionnaire to seek probability and to analyze variable cause event. As a result of FTA method was obtained a very high probability of lateness with the main cause event was classified into 4 groups, were caused by owner, caused by supervising consultants, caused by contractor, and caused by environment circumstances. From four of those main causes was obtained some results, first of all from owner’s perspective were a lot of assignment alteration and late payment installment to contractor, second of all from supervising consultants’ perspective was a checklist survey result in certain area, the contractor’s work could not be continued because of such a certain things, third of all from contractor’s perspective was caused by inaccurate work method, and the last of all from environment circumstances was the local people felt so agitated because of the project location to close to them.